Investigation of Variations of Invertase and Glucose Oxidase Degrees against Heating and Timing Options in Raw Honeys - Huseyin Sahin; Sevgi Kolayli; Mehmet Beykaya (Journal of Chemistry)
Invertase and glucose oxidase are secreted by the hypopharyngeal glands of honeybees for the hydrolysis of sucrose and the preservation from microbial effects, respectively. It is also prominent to understand how the levels of invertase and glucose oxidase of raw honey samples are being influenced by different conditions because the behavior of these specific enzymes in raw honeys could be a marker for the quality parameters. On the basis of this expectation, three raw honey samples tagged as blossom, pine, and oak were investigated. To reach the desired aim, extraction conditions were diversified by the range of different periods as 0, 1, 3, and 6 h and of different temperatures as 24, 45, and 65°C. The optimal heating condition and the period of extraction for invertase activity of all honey types were 24°C and 1 h because data of this condition were 147.960–178.266 enzyme unit per kilogram (U/kg) and 20.179–24.313 invertase number (IN). Although the variety of glucose oxidase activity was not evaluated as a worthwhile indicator of quality for raw honey due to its abnormal activity behavior, the change of invertase activity should be considered as a quality parameter due to showing the gradual decreasing level from initially a quite high one.